(untitled) (Eurasian Medical Research Periodical, 2024)
Currently, intestinal functional disorders are the most common pathology among patients with a gastroenterological profile.The study was conducted in the department of gastroenterology of the multidisciplinary medical center of Bukhara region, and 157 patients treated in the inpatient setting with IBS were selected. Patients with IBS were divided into two groups: non-refractory (ITSn – 68 patients) and refractory (IBSr – 89 patients) of IBS. Depending on the expression of clinical symptoms, patients with IBSn-d (diarrhea) - 38 (24.2%), IBSn-c (constipation) - 30 (19.2%), IBSr-d - 47 (29.9%) and IBSrc was allocated to 42 people (26.7%). The results of personal research showed that in irritable bowel syndrome, which is considered a functional disease of the intestine, the imbalance of cytokines is considered to be of great importance, especially this imbalance is characterized by a decrease in the amount of anti-inflammatory cytokine IL-10.